The Infiltration of Neutrophil Granulocytes Due to Loss of PTEN Was Associated with Poor Response to Immunotherapy in Renal Cell Carcinoma - Wu F; Chen J; Yao K; Fan D; Wang M; Liu Y; Xin S; Sun Z; Li S; Sun Y; Liu Q (Dove Medical Press, 2022)
Fei Wu,1- 3,* Jie Chen,4,* Kang Yao,1 Daming Fan,5 Minglei Wang,2 Yongjun Liu,1 Shouhu Xin,1 Zeqiang Sun,1 Shun Li,1 Yang Sun,6 Qingyong Liu1 1Department of Urology, the First Affiliated Hospital of Shandong First Medical University, Shandong First Medical University and Shandong Academy of Medical Sciences, Jinan, 250014, People's Republic of China; 2Shandong Provincial Key Laboratory of Radiation Oncology, Shandong Cancer Hospital and Institute, Shandong First Medical University and Shandong Academy of Medical Sciences, Jinan, 250117, People's Republic of China; 3Department of Urology, Shandong Provincial Hospital, Shandong First Medical University, Jinan, 250021, People's Republic of China; 4Department of Urology, Jinan Central Hospital, Cheeloo College of Medicine, Shandong University, Jinan, 250013, People's Republic of China; 5Department of Pathology, Jinan Central Hospital, Cheeloo College of Medicine, Shandong University, Jinan, 250013, People's Republic of China; 6Department of Dermatology, Qilu Hospital, Cheeloo College of Medicine, Shandong University, Jinan, 250012, People's Republic of China*These authors contributed equally to this workCorrespondence: Yang Sun; Qingyong Liu, Email sunyang@qiluhospital.com; liuqingyong@sdhospital.com.cnIntroduction: A primary impediment to the efficacy of immune checkpoint inhibitors is the lack of biomarkers for therapeutic responses and prognosis. Although patients with clear cell renal cell carcinoma (ccRCC) could be precisely selected for targeted therapy based on somatic mutations, it remains controversial to choose the suitable patients with a high response rate to immune checkpoint inhibitors (ICIs). The immune-dependent roles of tumor suppressor PTEN in the formation of tumor immune microenvironment remain elusive.Methods: We comprehensively analyzed the genomic and transcriptomic data from multiple ccRCC datasets, including bulk-RNA sequencing and single-cell RNA sequencing data. In vitro, immunoblotting, qRT-PCR, and RNA sequencing were conducted in ccRCC cell lines upon PTEN depletion. Gene ontology and gene set enrichment analysis were performed to screen the critical pathway and molecules in response to PTEN deletion. Immunohistochemistry staining and further bioinformatic analysis were used to validate our data.Results: Based on multi-omics analysis of public datasets of renal cancer, the frequently mutated or deleted PTEN was found to be correlated with a suppressive tumor immune microenvironment in ccRCC. Furthermore, we depleted PTEN via CRISPR-Cas9 in Caki-1 cells, which led to the upregulation of multiple neutrophil chemokines, particularly CXCL1, CXCL2, CXCL5, CXCL6, and CXCL8. The roles of neutrophil chemokines and neutrophil markers were further validated and investigated for the association with prognosis in vitro, clinical samples, and the publicly available databases. The expression of CXCL1, CXCL8, and neutrophil markers, S100A9 and BCL2A1, were significantly associated with a poor immunotherapy-related prognosis in public dataset of renal cancer patients receiving ICIs treatment.Conclusion: These results add a new layer to understanding the association between PTEN status and the role of neutrophil infiltration in ccRCC. Moreover, our findings propose low expression of PTEN as candidate factor of resistance to anti-PD-1-based immunotherapy in ccRCC.Keywords: PTEN, kidney cancer, CXCL1, renal cancer, prognosis